Comparison of the Outcomes Between Coronary No-Reflow and Slow-Flow Phenomenon in Non-Stemi Patients - Umair Abrar, Javed Khurshed Shaikh, Iftikhar Ahmed, Ahsan Raza, Gulzar Ali Buriro, Syed Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coronary slow flow phenomenon (CSFP) and coronary no-reflow phenomenon (CNP) have the potential to raise the risk of severe cardiovascular adverse events (MACE). Objectives: This study's goal was to evaluate and contrast the clinical outcomes after a year for CNP and CSFP patients who received PCI for a non-ST elevation myocardial infarction (NSTEMI). Methods: In this research, 95 patients had NSTEMI and had PCI within 24 hours after symptoms started. An angiographic characteristic of the infarct-related artery's TIMI flow was used to divide patients into two groups: the CSP group (n=85) and the CNP group (n=10). Patients were tracked for a full year. To be statistically significant, the p-value needed to be <0.05. Results: There were 95 patients with NSTEMI included in this research (66 males; mean age: 62.71±13.70). CNP was seen in 10.5% (n = 10) and CSFP in 89.4% (n = 85) of NSTEMI patients, respectively. we provide the results of our demographic analysis. Conclusion: When comparing CNP and CSFP patients with NSTEMI, the clinical results and risk of stroke are worse for CNP individuals.